Management Strategy for Business Sustainability Under Macro Effects In An Econometric Model – Case of PKN Orlens in Oil and Gas Industry in Poland - HA, TRAN THI HOANG; ANH, PHAM TUAN (The journal of contemporary issues in business and government, 2021)
The Poland economy has gained lots of achievements esp. in gas and oil industry during the 2014-2019 period and affected by Covid 19 and US-China trade war. Orlens group is a big gas and oil group operating in Central Europe countries such as Germany, Poland, Czech and Lithuania. This paper measures the revenue and EBITDA of a big gas and oil company, PKN Orlens in Poland, under impacts of macro indicators. As we experienced role of business management and sustainable development in gas and oil industry has been increasing with new perspectives in management, corporate governance models.In order to recommend for sustainable business development, this research paper aims to figure out how much effects in revenue from macro indicators of one of big listed Poland firms, PKN Orlens during the period 2014-2019 with semiannual data. Our findings show that revenue are affected much more by exchange rate and lending rate. It implies bank system policies and macro policies. JEL classification numbers: M21, M1, G12, G30